Electro-Hydraulic Transient Regimes in Isolated Pumps Working as Turbines with Self-Excited Induction Generators - Filipe C. Madeira; João F. P. Fernandes; Modesto Pérez-Sánchez; P. Amparo López-Jiménez; Helena M. Ramos; P. J. Costa Branco (Energies, 2020)
The use of pumps working as turbines (PATs) is a sustainable technical measure that contributes to the improvement of energy efficiency in water systems. However, its performance analysis in off-grid recovery systems is a complex task that must consider both hydraulic (PAT) and electrical machines (typically a self-excited induction generator-SEIG). Aside from several kinds of research that analyze the PAT-SEIG behavior under steady-state constant hydraulic and electrical conditions, this research focuses on the analysis of PAT-SEIG transient regimes, by analyzing their variation when a sudden change occurs in the hydraulic or electrical components. Analytical models were developed to represent the operation of SEIG, PAT, and the PAT-SEIG coupled system. Hydraulic and electromechanical experimental tests validated these models. An excellent fit was obtained when analytical and experimental values were compared. With these models, the impact on the operation of the PAT-SEIG system was examined when sudden change occurred in the excitation capacitances, resistive loads, or recovered head. With a sudden increase of resistive load, the hydraulic power and SEIG stator current remain almost constant. However, there is an increase of SEIG reactive power, decreasing the PAT-SEIG efficiency. Also, with a sudden increase of SEIG capacitors or PAT hydraulic head, the SEIG stator current increases once and not again, while PAT-SEIG efficiency decreases, but the induction generator can be overloaded. The development of this research is key to the advancement of future models which can analyze the coupling of micro-hydropower solutions.